Estimación de factores que influyen en la elección modal de transmetro, taxi-colectivo o bus en la Avda. Murillo en Barranquilla (2018)
The present investigation focused on evaluating the factors that influence on the choice of public transport mode at the “Calle 45” or Murillo Avenue, considering the “Taxi-colectivo” (is like a pool taxi type) as a non-formal transport way in Barranquilla District. To estimate these factors, the econometric models of the multinomial logit type were used, based on the information collected through face-to-face surveys of revealed and declared preferences, seeking to know a user’s behavior in hypothetical situations, placing as a reference the modes attributes of: travel time, waiting time, cost and citizen-social security; Based on these estimates, a few policies are recommended for the improvement of the transport situation in this important place of the city, primarily because of the high presence of non-formal alternatives transport way.